2019
DOI: 10.1016/j.celrep.2019.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Anabolism Plays a Critical Role in Pancreatic Cancer by Coupling Carbon and Nitrogen Metabolism

Abstract: SUMMARY Glutamine is thought to play an important role in cancer cells by being deaminated via glutaminolysis to α-ketoglutarate (aKG) to fuel the tricarboxylic acid (TCA) cycle. Supporting this notion, aKG supplementation can restore growth/survival of glutamine-deprived cells. However, pancreatic cancers are often poorly vascularized and limited in glutamine supply, in alignment with recent concerns on the significance of glutaminolysis in pancreatic cancer. Here, we show that aKG-mediated rescue of glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 48 publications
10
106
2
Order By: Relevance
“…The deprivation of PDA tumor cells of nutrients may also change over time, as tumor growth reshapes 3D cellular organization and the proximity of cancer cells to stroma and endothelial cells. It is therefore not surprising that, unlike Bott et al (34), we found no significant association between average GS levels and tumor grade or patient survival (Fig. S13).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The deprivation of PDA tumor cells of nutrients may also change over time, as tumor growth reshapes 3D cellular organization and the proximity of cancer cells to stroma and endothelial cells. It is therefore not surprising that, unlike Bott et al (34), we found no significant association between average GS levels and tumor grade or patient survival (Fig. S13).…”
Section: Discussioncontrasting
confidence: 69%
“…Nevertheless, based on our results and those of Bott et al (34), targeting GS in the nutrient-deprived PDA tumors holds significant therapeutic value in pancreatic cancer.…”
Section: Pda Cells Adapted To Nutrient-deprived Conditions Are Sensitsupporting
confidence: 70%
“…In addition to KRAS, other genetic alterations related to amino acid metabolism enzymes have been implicated in the pathogenesis of PDAC. Genetic ablation of Bcat2 , endothelial NOS ( eNOS ), and glutamate ammonia ligase ( GLUL ) could attenuate PanIN progression ( 23 , 83 , 84 ). Moreover, genetic alterations have also been demonstrated to drive tumorigenesis through coupled metabolic and epigenetic reprogramming.…”
Section: Amino Acid Metabolism Regulates Pdac Development and Progresmentioning
confidence: 99%
“…Targeting cancer metabolism is a promising therapeutic strategy, and metabolic reprogramming driven by oncogenes enables PDACs to survive in hypoxic and nutrient-deprived microenvironments [ 11 ]. For example, oncogenic KRAS, present in more than 95% of PDAC tumors, upregulates glutamine metabolism for supporting its biosynthetic needs and maintaining redox homeostasis [ 12 , 13 ]. Glutamine is indispensable for PDAC growth as it serves as a carbon donor for TCA cycle anaplerosis and nitrogen donor for nucleotide biosynthesis and amino acid generation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%